2016
DOI: 10.1371/journal.pone.0166032
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Family on Adolescent Sexual Experience: A Comparison between Baltimore and Johannesburg

Abstract: The main objective of this paper is to understand the role of the family on the sexual experiences of adolescents from urban, disadvantaged settings in Baltimore and Johannesburg. Data were collected as part of the WAVE study, a global study of disadvantaged youth in five cities. Qualitative data were based on key informant interviews, a Photovoice exercise, community mapping, focus groups and in-depth interviews with adolescents. Quantitative data were gathered from an ACASI survey that was administered to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
4
29
0
2
Order By: Relevance
“…The positive association between self-esteem and positive sexual behaviours have been well established. Similar to other studies [ 30 ], the influence of family structure on sexual debut of adolescents was stronger for females than it was for males. This means that factors that protect females are different from factors that protect males.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The positive association between self-esteem and positive sexual behaviours have been well established. Similar to other studies [ 30 ], the influence of family structure on sexual debut of adolescents was stronger for females than it was for males. This means that factors that protect females are different from factors that protect males.…”
Section: Discussionsupporting
confidence: 88%
“…Although risk and protective factors are well-known, the interaction between these two factors is not completely understood. The literature has shown that some adolescents who reside up in single-parent households amid poverty and little monitoring or support do not become involved in risky behaviours [ 30 , 31 ]. These conclusions imply that some protective factors working concurrently with risk factors may offset and even contradict the most harmful effects of negative factors.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed factors associated with higher knowledge of safe sex were living with people other than parents, studying family planning and belonging to a religion that accepted the use of birth control. While parents may be an important source of information on sexual and reproductive health at some stages of adolescence, living more independently may reflect other opportunities for gaining knowledge and experience in these matters [29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The increased probability of delaying sexual debut among teenagers living with both parents' supports can be explained by the fact that female teenagers may be closer with family members compared to males, put more meaning on the family relationships and consequently more affected by changes and disruption in family structure (Mmari et al, 2016). Some research suggests that girls with absent fathers are susceptible to having unstable and conflicted parental relationships, which correspondingly influence accelerated pubertal maturation (Mendle et al, 2009).…”
Section: Discussionmentioning
confidence: 99%